METHOD FOR DETERMINING THE POSITION OF THE POINTS FOR ATTACHMENT OF WARP AND BACKSTROPS TO TRAWL BOARDS - V. I. Gabryuk; V. V. Kudakaev; L. A. Gabryuk (Известия ТИНРО, 2020)
Technique for analytical determining where the warp and backstrops should be attached to trawl board is proposed. The algorithm is developed for both triangular and quadrangular arrangement of the backstrops. Equations for calculation of the backstrops length are presented. Equilibrium stability conditions are defined for trawl doors.